A Novelly Developed Bipolar Needle Knife Can Be an Alternative Device Choice for Endoscopic Submucosal Dissection (With Video) - Chen, Shengsen; Zhou, Danping; Yu, Jiangping; Ruan, Rongwei; Liu, Yuanshun; Li, Yandong; Shen, Qiwen; Wang, Shi (Frontiers in Medicine, 2022)
Background: Endoscopic submucosal dissection (ESD) is technically difficult with high rates of complications, such as perforation and bleeding. We aimed to explore the safety and cutting efficiency of a novelly devised bipolar knife for ESD procedure. Methods：Taking a traditional monopolar knife as reference, the safety and feasibility of the novel bipolar knife were evaluated by an animal experiment and a hunman study. Furthermore, we assessed the usefulness and advantage of this novel bipolar knife by using finite element method. Results：A porcine experiment confirmed that there was no significant difference in wound size and cutting speed between the monopolar and bipolar knives. The thermal damage and histopathological scores produced by the two knives were similar. Additionally, the porcine experiment and patinets’ study identified that the incidence of postoperative complications such as bleeding, perforation and infection had no statistical difference between the monopolar and bipolar groups. Finally, the finite element model showed that the length and depth of thermal damage caused by the bipolar knife were respectively 102.77-117.98% and 80.87-84.53% of those caused by the monopolar knife at the same power. Conclusion：The novel bipolar knife was theoretically safer than the monopolar knife, and at least was confirmed not inferior to monopolar knife in operability and cutting efficiency. Thus the novel bipolar knife can be an alternative device choice for ESD.